The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3329/bjvm.v14i2.31398
|View full text |Cite
|
Sign up to set email alerts
|

Serological Prevalence of Ovine and Caprine Brucellosis in Bangladesh

Abstract: Brucellosis is considered to be the most widespread zoonosis throughout the world. It has a serious implication on human health as well as on the economic development in a developing country like Bangladesh. The objective of the present study was to determine the seroprevalence and to delineate the risk factors for Brucella seropositivity in small ruminants in Mymensingh district of Bangladesh. In the present study, serum samples were collected from a total of 2456 small ruminants (1710 goat and 746 sheep) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The migration of animals through porous borders from neighbouring countries is reported (Annual report, 2018(Annual report, -2019. Prevalence of 9.80% small ruminant brucellosis from Pakistan (Arshad et al, 2011) and 9.53% from Bangladesh (Shafy et al, 2016) indicate other probable route/s of disease transmission through migration of animals via porous border into the country. Hence, policy for preventing the entry of the animals, strengthening quarantine measures and testing at the borders will help to prevent the disease incursion into the country.…”
Section: Middle East Regions Are Regularly Reporting B Meletensis Infectionmentioning
confidence: 99%
“…The migration of animals through porous borders from neighbouring countries is reported (Annual report, 2018(Annual report, -2019. Prevalence of 9.80% small ruminant brucellosis from Pakistan (Arshad et al, 2011) and 9.53% from Bangladesh (Shafy et al, 2016) indicate other probable route/s of disease transmission through migration of animals via porous border into the country. Hence, policy for preventing the entry of the animals, strengthening quarantine measures and testing at the borders will help to prevent the disease incursion into the country.…”
Section: Middle East Regions Are Regularly Reporting B Meletensis Infectionmentioning
confidence: 99%
“…Higher prevalence of bovine brucellosis (10%) was reported by [25] in Lebanon. Lower prevalence of caprine brucellosis (9.53%) by using RBPT, was reported by [26] in Bangladesh. They also reported higher percentage of ovine brucellosis (9.92%).…”
Section: Prevalence Of Bovine Ovine and Caprine Brucellosis In North ...mentioning
confidence: 72%
“…Difference in seroprevalence according to city might be related to the number of animals related to the grazing The antibodies detected in males were higher than in females. Shafy et al (2016) recorded that the prevalence among females (39.2%) is higher than males (18%), it may be linked to the interaction of other risk factors that might af prevalence of the antibodies among sheep and it need further investigation. Age wise percentage with Shafy et al (2016) who reported that the percentage in adults (57%) was higher than in young animals (8.1%), lowered incidence among animals may be owed to the immunization acquired by maternal immunoglobulins.…”
Section: Discussionmentioning
confidence: 98%
“…Shafy et al (2016) recorded that the prevalence among females (39.2%) is higher than males (18%), it may be linked to the interaction of other risk factors that might af prevalence of the antibodies among sheep and it need further investigation. Age wise percentage with Shafy et al (2016) who reported that the percentage in adults (57%) was higher than in young animals (8.1%), lowered incidence among animals may be owed to the immunization acquired by maternal immunoglobulins. Previous literature that with exception of age, no other factors had an effect on the percentage of brucellosis in sheep, neither for RBPT-nor for SAT-seroposit (Abdallah et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation